The Influence of Artificial Intelligence on Organizational Performance: Mediation of Employee Productivity in the Greater Jakarta Area - Imron Jarjuni; Didin Hikmah Perkasa (Dinasti Publisher, 2025)
This study aims to examine the influence of artificial intelligence (AI) on organizational performance, considering employee productivity in the Greater Jakarta area, Indonesia, as a mediating variable. This study is a quantitative study with purposive sampling as the sampling method. The 200 respondents were men and women, employees in the Greater Jakarta area, aged between 18 and 55 years old, who were accustomed to using AI to support their work. Primary data was obtained through a questionnaire distributed online via Google Form. This study used closed-ended questions with a Likert scale as a measurement method, namely a scale of 1-5. SmartPLS version 4 was used as a data analysis tool with the Partial Least Squares technique. The results showed that there was a significant effect between the artificial intelligence variable and organizational performance through employee productivity.